Growth and hormonal status of children treated for acute lymphoblastic leukaemia. - Swift, P G (1978)
Growth and hypothalamic-pituitary function have been studied in children in long-term remission from acute lymphoblastic leukaemia (ALL). All 14 children are growing and developing normally; in the 8 children in whom the hypothalamic pituitary axis was investigated endocrine function is normal. Continuing long-term review of these children is essential, but hypothalamic-pituitary investigation is required only when there is a decrease in growth velocity or delay in the onset of puberty.